2020
DOI: 10.1097/acm.0000000000002987
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Professionalism in Postgraduate Medical Education: A Systematic Review

Abstract: Purpose This systematic review sought to summarize published professionalism curricula in postgraduate medical education (PGME) and identify best practices for teaching professionalism. Method Three databases (MEDLINE, Embase, ERIC) were searched for articles published from 1980 through September 7, 2017. English-language articles were included if they (1) described an educational intervention addressing professionalism, (2) included postgraduate medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 61 publications
0
35
0
2
Order By: Relevance
“…Despite a small second follow up sample, we found that some changes persisted three months after the intervention. Previous research also reveals that educational interventions in teaching professionalism can be successful [1,26,27]. Even though our study revealed that this educational intervention was successful in improving attitudes, subjective norms, perceived behaviour control and intentions, it is important to note that the effectiveness of the intervention depended on the complexity of the behaviour and participants' characteristics.…”
Section: Changes In Professional Behavioursmentioning
confidence: 47%
See 2 more Smart Citations
“…Despite a small second follow up sample, we found that some changes persisted three months after the intervention. Previous research also reveals that educational interventions in teaching professionalism can be successful [1,26,27]. Even though our study revealed that this educational intervention was successful in improving attitudes, subjective norms, perceived behaviour control and intentions, it is important to note that the effectiveness of the intervention depended on the complexity of the behaviour and participants' characteristics.…”
Section: Changes In Professional Behavioursmentioning
confidence: 47%
“…Teaching professionalism, however, is largely researched at undergraduate level and lacks the use of theoretical models (see systematic reviews [1,26]). A recent systematic review on teaching professionalism in postgraduate training concluded that formal, structured teaching can improve professionalism in medical trainees but it also found that the majority of studies were conducted within one institution and just one fifth of eligible studies included controlled groups [27]. The current study overcomes these limitations and adds to existing knowledge by presenting the findings from a high quality mixed methods study evaluating an educational intervention based on the theoretical model and using data from geographically spread multiple locations.…”
Section: Changes In Professional Behavioursmentioning
confidence: 96%
See 1 more Smart Citation
“…EPAs, a relatively new concept in medical education [3], are addressed by accreditation graduate medical councils such as ACGME (Accreditation Council for Graduate Medical Education) [4]. They are addressed in competency frameworks such as CanMEDS (the Canadian competency framework introduced by The Royal College of Physicians and Surgeons of Canada [5,6] too.…”
Section: Introductionmentioning
confidence: 99%
“…As the authors of this review have concluded, finding best practices based on synthesizing previous findings, which were very heterogeneous, was difficult. It is also concluded that "even simple, short teaching sessions" would affect professionalism [6].…”
Section: Introductionmentioning
confidence: 99%